Relationship between the Presence of the nalC Mutation and Multidrug Resistance in Pseudomonas aeruginosa - Nourkhoda Sadeghifard; Azar Valizadeh; Mohammad Reza Zolfaghary; Mohammad Hossien Maleki; Abbas Maleki; Reza Mohebi; Sobhan Ghafourian; Afra Khosravi (International Journal of Microbiology)
Objectives. The current study was conducted to determine the relationship between the presences of significant multidrug resistance in Pseudomonas aeruginosa (P. aeruginosa) having intact mexR genes (nalC) to different antibiotics. Methods. In order to identify nalC, fifty strains of P. aeruginosa were obtained. All isolates were found in urinary tract infections. They were evaluated against different antibiotics. The nalC mutant was identified by PCR. Results. The 50 clinical isolates of P. aeruginosa originated from two hospitals in Iran, in which 32 isolates were found in Milad hospital, and 18 isolates were collected in the Ilam Hospital. The results in Milad hospital of nalC revealed that all P. aeruginosa resistant to oxacillin showed the presence of nalC. In Ilam hospital only three (16.6%) isolates were resistant to oxacilin and aztreonam, and among these three isolates only one isolate revealed resistance to ceftazidime and amikacin. The resistant isolates showed the presence of both OXA-10 and nalC. Conclusion. Our results showed that the presence of nalC was observed among P. aeruginosa resistance to oxacilin. Thus, the finding suggested relationship between oxacilin resistance and presence of nalC and consequently overproduction of the MexABOprM efflux system.